An examination on causes for anxiety and depression among elderly people - SHREE, MS. K.C. RAJA; MS. PRIYA. S, (The journal of contemporary issues in business and government, 2020)
In India, the elder population is one of the fastest growing populations among the world. India has about 110 million of ageing citizens which ranks to the second largest global population and therefore by 2050, it is expected to raise up to 240 million. These elderly people are easily prone to get affected by some mental health problems, in which depression along with anxiety affects their total health and reduces their quality of life. This study identifies some of the factors that contribute to anxiety and depression in elderly people are Loss of pleasure, dependency, self-confidence, isolation, medical conditions, financial status, memory problems, sufferer, identity and physical limitations, death fear, loneliness and being treated badly. Among those factors, loss and sleeping disturbances greatly contribute to the reasons that cause anxiety and depression in elderly people. Future studies to be conducted for the preventive measures for anxiety and depression among elderly people. Some innovation in preventive measures should be implemented to reduce depression and anxiety among elderly people.